2014
DOI: 10.1890/140068
|View full text |Cite
|
Sign up to set email alerts
|

Wild state secrets: ultra‐sensitive measurement of micro‐movement can reveal internal processes in animals

Abstract: Assessment of animal internal “state” – which includes hormonal, disease, nutritional, and emotional states – is normally considered the province of laboratory work, since its determination in animals in the wild is considered more difficult. However, we show that accelerometers attached externally to animals as diverse as elephants, cockroaches, and humans display consistent signal differences in micro‐movement that are indicative of internal state. Originally used to elucidate the behavior of wild animals, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 30 publications
(53 reference statements)
1
55
0
Order By: Relevance
“…In these situations, human observers are superior because they are able to acquire additional information (e.g., posture of ears, body tension, external stimuli) that facilitate correct discrimination. Unfortunately, we lacked this information with our sensors, although techniques like measurements of micromovements [29] or heart beat [30] promise to fill this gap soon. Additionally, animals sometimes gradually transition from one state to another or display active behaviors (e.g., grooming) after lying down.…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, human observers are superior because they are able to acquire additional information (e.g., posture of ears, body tension, external stimuli) that facilitate correct discrimination. Unfortunately, we lacked this information with our sensors, although techniques like measurements of micromovements [29] or heart beat [30] promise to fill this gap soon. Additionally, animals sometimes gradually transition from one state to another or display active behaviors (e.g., grooming) after lying down.…”
Section: Discussionmentioning
confidence: 99%
“…Our group previously attached accelerometers in collars to African elephants at Disney's Animal Kingdom ® , showing that common elephant behaviors (resting, feeding, bathing, and walking) can be differentiated from one another using dynamic acceleration and the periodicity of movement (Soltis et al 2012). We also showed that elephants walk with a different posture dependent on whether they are in a positive or negative emotional state (Wilson et al 2014). …”
Section: Introductionmentioning
confidence: 90%
“…An animal's internal state relates to the physiological and psychological drivers of movement [7,34]. This includes desire to eat, find shelter, find mates, escape predation or avoid competition.…”
Section: Internal Statementioning
confidence: 99%